A LEADERSHIP TRADITION IN MADURESE FISHING COMMUNITY IN PANARUKAN - Wati, Diah Ismoyo (LITERASI: Jurnal Ilmu-Ilmu Humaniora, 2011)
Based on field research, this article discusses maritime leadership principle in Madurese fishing community, in Panarukan, Situbondo, East Java. This community has a unique tradition called as toron tompaâan. In this tradition, juragan laut (a ship leader) will feel very ashamed and decide to resign from his position if he failed in getting more fishes, especially cob fish. Although for reaching the position as juragan laut needs hard works and strict step by step mechanism with good achievement, he decide to resign because such failure means he, as a leader, cannot give enough livelihoods to the crews and juragan darat (a ship owner). For Indonesian context, the resign tradition in toron tompaâan will give a good teaching for political and governmental elites who never have such tradition when they made fatal failure in conducting the governance. Further, the tradition will be suitable value for making Indonesia better and more democratic. Keywords: Madurese fishing community, Panarukan, toron tompaâan